2014
DOI: 10.1371/journal.pone.0093518
|View full text |Cite
|
Sign up to set email alerts
|

Alpha, Beta and Gamma Diversity Differ in Response to Precipitation in the Inner Mongolia Grassland

Abstract: Understanding the distribution pattern and maintenance mechanism of species diversity along environmental gradients is essential for developing biodiversity conservation strategies under environmental change. We have surveyed the species diversity at 192 vegetation sites across different steppe zones in Inner Mongolia, China. We analysed the total species diversity (γ diversity) and its composition (α diversity and β diversity) of different steppe types, and their changes along a precipitation gradient. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…In line with this result, the study conducted at two sites in Nepal found significant variation in woody species composition between northeast and southwest facing slopes [28]. This pattern may also indicate the indirect impact of altitudinal gradients and topographic aspects on the species composition by limiting the habitat quality and suitability such as soil fertility, precipitation and temperature to support the vegetation which thereby shape the spatial structure of the community assemblages [29][30][31][32][33]11]. Moreover, our study is in congruent with the findings of the previous studies [33][34][35][36] that indicated the effect of altitude gradient on species composition.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In line with this result, the study conducted at two sites in Nepal found significant variation in woody species composition between northeast and southwest facing slopes [28]. This pattern may also indicate the indirect impact of altitudinal gradients and topographic aspects on the species composition by limiting the habitat quality and suitability such as soil fertility, precipitation and temperature to support the vegetation which thereby shape the spatial structure of the community assemblages [29][30][31][32][33]11]. Moreover, our study is in congruent with the findings of the previous studies [33][34][35][36] that indicated the effect of altitude gradient on species composition.…”
Section: Discussionsupporting
confidence: 57%
“…Here, the species composition may be determined by the ecological processes such as environmental filters, biotic interactions and species specific neutral mechanism properties such as dispersal limitation [20,30,37,38]. Specifically, the variation in edaphic and microclimatic factors across spatial scales, altitude gradient and the topographic aspects differently affect the species adaptability and thereby the composition structure and distribution as this was also found by the previous findings from China and South Africa [11,12,35]. In line with this, our results pointed out that the majority of the rare species are specific to each site that may attribute towards the heterogeneities in species composition among these sites.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Yet knowledge gaps remain on the relative importance of these different drivers of 54 species richness at intermediate or landscape scales-the scales at which management decisions are most often made (Heikkinen and Birks 1996;Niemelä 1999;Koivula 2001 Haslem and Bennett 2008). As landscape heterogeneity increases within a given area, the amount of between-habitat (beta) diversity of species within that area is likely to increase (Tews et al 2004;Zhang et al 2014). This is one common explanation for species-area relationships: as the area sampled increases, so does the number of different habitats (Williams 1964;McGuinness 1984;Boecklen 1986;Olszewski 2004).…”
Section: Introductionmentioning
confidence: 99%
“…By definition, the mean alpha diversity (number of different species per site sampled) in landscapes with more preferred habitat is higher. A greater extent of the preferred habitat type will support more individuals, which through passive sampling will include more species (Osman 1977;Connor and McCoy 1979;McGuinness 1984;Maron et al 2013;Zhang et al 2014). …”
Section: Introductionmentioning
confidence: 99%